Cognitive friendship and goal management for the social IoT. (February 2017) - Kasnesis, Panagiotis; Patrikakis, Charalampos Z.; Κogias, Dimitris; Toumanidis, Lazaros; Venieris, Iakovos S.
Highlights: Use of smart software agents for enabling SIoT in the cloud. Definition of the smart object's profile and life cycle. Use of two ontologies for handling the social relationships of the smart entities. Manifest needs and services of smart objects through an embedded descriptive file. Presentation of an IoT scenario on our SIoT simulator using semantic rules. Abstract: The concept of an Internet of Things is already mature, enough to start evolving towards an Internet of Everything, over which humans, objects and virtual items can be interconnected. For this to be feasible though, there is the need for a framework which not only supports the interconnection between the entities of this Internet, but also allows the meaningful interaction between them. In this paper, we present an idea on how this can be materialized, based on the use of semantic web technologies and smart software agents. These middleware technologies, combined with machine learning techniques, can lead to cognitive friendship and goal management. The paper includes a presentation of the theoretical framework, a use case scenario, and results over the use of a simulation tool. Graphical abstract: